Automated Chicken Balance Technology To Reduce The Risk Of Death In The Chicken Weigh-In Process - Rika Apriliana; Igoh Iqbal Pratama; Ansory Makruf; Resza Alfiansyah; Desriyanti Desriyanti (Muhammadiyah University, Sidoarjo, 2022)
The chicken of the pemeats or broillaries is an excellent breed of highly productivity controlledby the chicken in the production of meat. These broillaries have been popular in Indonesia since the 1980swhere the powerholders created a grass-consumption program. Only 5-6 weeks of chicken can be harvested.At the chicken farm in the pijeran village owned by Mr. Lucky Bahar and the chicken weighted by hand, bytying the chicken feet and hanging the chicken upside down when weighed. This treatment often results inbruising and disfigured parts of the chicken's body especially in the leg. Apart from physical defects,chickens often experience stress that causes chicken death. This results in loss and loss of quality in thebroiler to be sold. From some of the problems experienced by the partner, we offer a technology that can beused to weigh chicken with more humane treatment by using arduino uno asa control and equipped with aservo motor that will be used to direct chickens to weigh areas. In addition to reducing defects and deathsin chickens, the farmer can weigh chickens in such large quantities that it takes time to know the weight andthe price of the entire chicken at a shorter time. Where a chicken at the gate of the servo will row thechicken to the transit area to be pointed at the scales. The chicken weighted only takes about 10 seconds andthen the LCD shows the total weight and the price of the chicken weighed.